The Mantu Bubak Tradition in Javanese Marriage Rituals from the Perspective of Soren Kierkegaard’s Existentialism - Muhadiyatiningsih, Siti Nurlaili; Wulan, Utami Cahyaning (Al Mudzakarah, 2025)
This study aims to examine community perspectives on the mantu bubak tradition in Sumberjo Village, Margomulyo District, Bojonegoro Regency, and to analyze the forms of human existence embodied in this tradition through the lens of Søren Kierkegaard’s existentialist philosophy. The research employs a qualitative approach with a fieldwork-based design. Data were collected through participant observation, in-depth interviews with traditional leaders, religious figures, and families involved in the practice of the tradition, as well as documentation. The data were subsequently analyzed using descriptive, hermeneutic, and interpretative approaches. The findings indicate that the majority of the community continues to perceive mantu bubak as a socially and culturally functional tradition, as it strengthens family ties, social solidarity, and mutual cooperation amid processes of modernization. From a Kierkegaardian perspective, this tradition represents the aesthetic, ethical, and religious stages of existence. Accordingly, mantu bubak can be understood as an existential expression of Javanese society in interpreting marriage not merely as a social event, but also as a moral and spiritual experience.